2015
DOI: 10.1002/eji.201445419
|View full text |Cite
|
Sign up to set email alerts
|

Arginase 1 activity worsens lung‐protective immunity against Streptococcus pneumoniae infection

Abstract: Type 2 helper cell (Th2) dominated chronic lung diseases such as asthma are characterized by an increased risk for bacterial lung infections. However, the underlying mechanisms are poorly defined. Arginase 1 (Arg1) has been suggested to play an important role in the pathophysiology of asthma, and is rapidly induced in lung macrophages by Th2 cytokines, thereby limiting macrophage-derived antimicrobial nitric oxide (NO) production. Here we examined the effect of Th2 cytokine induced upregulation or lung myeloid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 43 publications
(77 reference statements)
0
12
0
Order By: Relevance
“…Although MDSC depletion improved biofilm clearance by enhancing monocyte proinflammatory activity (12,14), the mechanism of action and whether Arg-1 was involved remained unclear. This was an important issue to address, since Arg-1 activity has been implicated in several types of cancers, Alzheimer's disease, and infection (18,24,35,36). In the current study, we used two mouse models of device-associated S. aureus biofilm infection to determine the role of myeloid-derived Arg-1 in shaping leukocyte infiltrates and promoting biofilm persistence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although MDSC depletion improved biofilm clearance by enhancing monocyte proinflammatory activity (12,14), the mechanism of action and whether Arg-1 was involved remained unclear. This was an important issue to address, since Arg-1 activity has been implicated in several types of cancers, Alzheimer's disease, and infection (18,24,35,36). In the current study, we used two mouse models of device-associated S. aureus biofilm infection to determine the role of myeloid-derived Arg-1 in shaping leukocyte infiltrates and promoting biofilm persistence.…”
Section: Resultsmentioning
confidence: 99%
“…However, the effects of MDSC Arg-1 on inhibition of T cell proliferation may be context dependent, as some studies have not demonstrated a role for the enzyme (33,34). Previous work reported that myeloid-derived Arg-1 expression has a pathological role in several cancers, Alzheimer's disease, and bacterial and helminth infections, establishing it as a key enzyme in dictating disease pathogenesis and immune outcomes (18,24,35,36). Therefore, elevated Arg-1 expression by MDSCs and/or macrophages may participate in preventing an effective immune response to S. aureus biofilm infection through the depletion of extracellular arginine and suppression of proinflammatory responses.…”
mentioning
confidence: 99%
“…Apart from intracellular bacteria, extracellular bacteria like Streptococcus pneumonia also modulate host arginase. S. pneumonia infection of alveolar macrophages induces arginase I expression in an IL-13-dependent manner, resulting in attenuated host defense against this pathogen during lung infection [31]. Similarly, Pseudomonas -infected lungs demonstrate a ~10-fold increase in arginase activity and a decrease in iNOS activity, leading to decreased production of NO [29].…”
Section: Alteration Of Arginine Metabolism By Pathogensmentioning
confidence: 99%
“…IL-5 and IL-13 are potent inducers of eosinophil chemotaxis in the lung (Pope et al, 2001) and IL-13 has been shown to be involved with M2 macrophage polarization causing depressed antibacterial immunity (Knippenberg et al, 2015). Therefore, we next studied these two innate type 2 effector cells.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, IL-13 induced M2 macrophages can cause reduced antibacterial immunity (Knippenberg et al, 2015). Recent data also suggest that development of acute exacerbations of infection is not caused by the acquisition of new strains but rather a clonal expansion of existing strains Stenbit and Flume, 2011).…”
Section: Discussionmentioning
confidence: 99%